Graphene nanoflakes with optimized nitrogen doping fabricated by arc discharge as highly efficient absorbers toward microwave absorption. (July 2019) - Zhou, Yuanliang; Wang, Ning; Muhammad, Javid; Wang, Dongxing; Duan, Yuping; Zhang, Xuefeng; Dong, Xinglong; Zhang, Zhidong
Abstract: Abundant resources, light weight as well as stable physicochemical properties enable carbon nanomaterials promising candidates toward microwave absorption. However, it is still a great challenge for carbon-based absorbers to achieve broad frequency bandwidth and strong absorption, which fundamentally ascribes to the poor impedance matching resulted by their comparatively high electrical conductivities. Herein, a feasible and high-yield method has been employed to the in-situ synthesis of N-doped graphene nanoflakes which can effectively address interfacial impedance mismatching, and realize the majority of microwaves penetration into the interior of absorber. The incorporation of substitutional N atoms into graphene lattices markedly weaken crystallization degree and introduce masses of defects, directly leading to the decline of electric conductivity, meanwhile benefiting the improvement of static magnetization. Our findings indicate that compared with pure graphene nanoflakes, the counterpart containing 4.6 at.% of nitrogen exhibits an excellent absorption capability, in which more than 99% of microwave energy can be quantitatively attenuated at 5–18 GHz. Experimental results coupled with theory calculations further elucidate that such high performance essentially originates from the proper impedance matching constructed in the N-doped graphene nanoflakes. Graphical abstract: Image 1091